Papilomavírus humano associado a lesões de cérvix uterina - CAVALCANTE, Vânia Lúcia Noronha (1997)
With the aim of improving our knowledge on the role of human papillomavirus (HPV) in the aetiopathogenesis of cervical cancer in Northern Brazil, it was studied the prevalence of HPV among 228 women with lesions of uterine cervix attending Ofir Loiola Institute, in Belem, Para, from March, 1992 to May, 1996. Histopathological examination was performed with all cervical biopsy sample obtained from these patients. In addition, specimens were analysed through different laboratory techniques to detect HPV DNA. The patients were assigned to three groups, according to the diagnosis made by histopathology, as follows: A, including women suffering from invasive epidermoid carcinoma or adenocarcinoma; B, 54 patients having either cervical intraepithelial neoplasia grade ll or lll (CIN ll or CIN lll); and C, involving 19 women with chronic cervicitis. Over all, the prevalence rates of HPV in groups A, B and C, as determine by PCR and/or dot-blot were 70.3%, 63.0% and respectively. HPV 16 predominated over other genotypes, accouting for 60.4% and 54.5% of types identified in groups A and B, respectively. Altogether HPV types 16, 18 and 33 were detected in 71.4% of positive HPV patients belonging to group C. The in situ hybridization (ISH) technique, including polyvalent HPV types 6/11, 16/18 and 31/33/35 specific probes, was used to examine 155 of the 228 samples tested by PCR, yielding HPV-positive results in 17.4% of them. Using this latter procedure, that is, PCR, the positivity rate was of much higher, 65.2%, than that of ISH. With regards to the potential HPV concurrent risck factors for the development of uterine cervical malignancies , it is noteworthy that 40% of women assigned to groups A and B reported having had first sexual intercourse when aged 15 years or less. During the interview, howewer, the number of lifetime sexual partners reported by most of them ranged from 1 to 3, suggesting lack of promiscuity among the sampled patients. In general, our data accord with those from other studies carried out throughout the world, indicating that HPV plays a significant role in the aetiology of both cervical inttraepithelial neoplasia and carcinoma of the uterine cervix. Further and broader investigations should however be carried out, in order to better understand the epidemiological features of HPV infection in the Amazon Region.